Modelling the movement of crowd evacuation using computational simulation technique - Noor Akma, Abu Bakar; Mazlina, Abdul Majid; Khalid, Adam; Allegra, Mario (2018)
Intelligence likewise the computational and simulation model. The technique consist the theories and concept which can be operated by the machine and important to realize that the computational method allows for creating, analyzing and experimentation. The most popular and well-known technique is Agent-based Simulation (ABS). ABS is able working in emergent phenomenon with the characteristic of individual agent behavior and movement. Whereas Social Force Model (SFM) has been used in last few decades and attracted the researchers in the crowd evacuation investigation. Hence artificial intelligence (AI) is advancing to produce more concise and interesting crowd behaviors but not guarantee to produce the realistic model. So, this research work investigates the three simulation techniques which are SFM, ABS and the hybrid of SFM/ABS in order to simulating the crowd evacuation of human pedestrian in the building using computational simulation tool. The research work has been started with the case study description and data collection. Secondly, the development of conceptual model and the implementation of the simulation models using the computational simulation tool. This research work aimed to have these three different computation simulation techniques and intended for the most appropriate and better simulation model as the expected results. Findings from this research work show that the proposed simulations model using the computational simulation techniques can assist developer and the researcher to implement the human movement of crowd simulation model (a case study of in the building on fire)